Making Economics of Piety: Fashion, Lifestyle and Identity in Pop-Islamism Turn - Fransisca Dwijayanti (Shirkah: Journal of Economics and Business, 2018)
The emergence of young Muslims since the last decade has led Muslim industry to grow rapidly into the market bringing new social era of Islamic fashion. What is the role of religious piety boosting the production the Muslim fashion industry? This article argues that Muslim fashion have embodied within economic part of religion. In addition, this glowing of the industry has been supported by the blooming of such factors as media (Muslim magazines), Muslim designers, Muslim communities, and Muslim fashion stores. The industry of Muslim fashion ultimately becomes one of the most promising industries in fashion retail in Indonesia and other Muslim majority countries.Â Keywords: Muslim fashion, lifestyle, market IslamÂ